Chinese Concept TANG PING / To Lie Flat in Russian Perception - Lijun Guo; Ziyu Wang (Научный диалог)
The article considers a new for the Chinese society philosophy of young people’s lifestyle represented by the concept of TANG PING (to lie flat). The study relevance is due to the tendency for emergence of words and expressions that represent new phenomena of reality in the Chinese language. It is noted that in 2021, the expression to lie flat has become popular in China, and the phenomenon that it designates has been actively discussed not only in everyday Internet communication, but also in the media. It is shown that several publications on this topic have also appeared in the Russian Internet discourse. The article analyzes the perception of the precisely translated Chinese expression to lie flat as a symbol of the contemporary Chinese culture by the Russians based on Internet texts and the online survey results. It is shown that the Chinese concept is closely related to the Russian literary phenomenon “Oblomovism”. There are presented the views of Chinese researchers on “Oblomovism” and its similarities and differences with the new phenomenon in the life of young generations of the Chinese society. The practical significance of the study lies in clarifying the semantic volume of the expression tang ping (to lie flat) as a linguistic unit naming a current phenomenon in the life of a modern developed society which has become widespread not only in China, but also in other countries.